2013
DOI: 10.1111/eip.12033
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life among adolescents: a comparison between subjects at risk for psychosis and other help seekers

Abstract: Adolescents at risk for psychosis have a poorer HRQoL index than other help seekers and they also differ in several sub-items, particularly in the lower scores in mental function. In the future, these findings should be considered in the care of adolescents at risk for psychosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
2
14
0
1
Order By: Relevance
“…According to previous findings and our previous studies, [25][26][27][28][29] we hypothesize that poor functioning ability is an independently associated factor for psychosis risk screening status. To our knowledge, there is no previous studies that have included all these associated factors and assessed how they may interact.…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…According to previous findings and our previous studies, [25][26][27][28][29] we hypothesize that poor functioning ability is an independently associated factor for psychosis risk screening status. To our knowledge, there is no previous studies that have included all these associated factors and assessed how they may interact.…”
Section: Introductionsupporting
confidence: 60%
“…14 Rietdijk et al reported that mood and anxiety disorders were present in 39.1% of those cases who had been treated in secondary mental health care before the onset of psychosis. [25][26][27][28] Finally, in a previous study of our earlier study sample, 29 we reported with a moderate sample size of 80 adolescents that lower functioning ability explained at-risk status to psychosis independently after age, gender, QoL and depression were adjusted. Other longitudinal studies (that have not been able to control for treatment effects) have found a tendency for symptom reduction, suggesting a worse mental state at baseline/initial presentation to mental health services.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…This is demonstrated by their high levels of hopelessness, depression, anxiety, and poor quality of life, in comparison to other help-seeking patients and patients with first-episode psychosis [30,31,95]. In fact, they often fulfill the diagnostic criteria for other mental disorders that require treatment, in particular depression, anxiety, and substance abuse or dependence [25,42,100].…”
Section: Need For Treatment In Clinical High Risk States Of Psychosesmentioning
confidence: 99%
“…In order to better understand the factors related to the worsening of sQoL in early psychosis, it is important to examine which features are already associated with poor sQoL in individuals presenting clinical high risk. Three studies have shown that sQoL is markedly lower in prodromal or At-Risk Mental State (ARMS) patients compared to healthy controls, 8 other help seekers 21 and FEP patients. 22 These findings lend support to the notion that this population is already in need for mental health care, especially considering their risk for transition to psychosis.…”
Section: Introductionmentioning
confidence: 99%